Corporate Social Responsibility (CSR) as an Effective and Sustainable Approach to Workplace and Community Relations - Azanza, Rodolfo T. (Philippine Journal of Labor and Industrial Relations; Vol 29 (2009): Philippine Journal of Labor and Industrial Relations, 2021)
No abstract